2007
DOI: 10.1039/b700371b
|View full text |Cite
|
Sign up to set email alerts
|

Atomic spectrometry update. Environmental analysis

Abstract: This is the twenty-third annual review published in JAAS of the application of atomic spectrometry to the chemical analysis of environmental samples. This update refers to papers published approximately between September 2006 and August 2007. In the analysis of air, there has been an increased awareness of the need to collect and characterise ultrafines, i.e. particles below 100 nm in size, and such work is being facilitated by the development of real-time aerosol mass spectrometric techniques. In the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 368 publications
(436 reference statements)
0
31
0
Order By: Relevance
“…Most of the analytical methods for Hg determination in solid samples are based on wet digestion followed by spectrometric quantification. [21,22] An environmental friendly alternative is the use of a reagent-free non-chemical method based on the thermal decomposition (pyrolysis) of solid samples. [23][24][25][26] The aims of this study were: (1) to evaluate the Hg contamination of soil and perennial plants in the urban area of Baia Mare, (2) to study the relationships between Hg in soil and plants, and between the contents of Hg, As, Cd, Cu, Pb, Zn and the properties of soils (pH, Total Organic Carbon (TOC)) using multivariate statistical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the analytical methods for Hg determination in solid samples are based on wet digestion followed by spectrometric quantification. [21,22] An environmental friendly alternative is the use of a reagent-free non-chemical method based on the thermal decomposition (pyrolysis) of solid samples. [23][24][25][26] The aims of this study were: (1) to evaluate the Hg contamination of soil and perennial plants in the urban area of Baia Mare, (2) to study the relationships between Hg in soil and plants, and between the contents of Hg, As, Cd, Cu, Pb, Zn and the properties of soils (pH, Total Organic Carbon (TOC)) using multivariate statistical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive database of literature and research on elemental speciation could be found at www.speciation.net, the official Web site of the European Virtual Institute for Speciation Analysis (EVISA; 2008). These advances have been also collected and described in various review articles during the last decade (Ali et al, 2005;Butler et al, 2005Butler et al, , 2006Butler et al, , 2007Butler et al, , 2008Cave et al, 2001;Li et al, 2008;Moldovan et al, 2004;Wang, 2007;Wuilloud & Altamirano, 2006;Yip & Sham, 2007). It is not our intention to perform an extensive literature review on analytical methods for elemental speciation, in general.…”
Section: Analytical Methods For the Determination Of Metal And Metallmentioning
confidence: 96%
“…The XRF method has a great advantage in being a direct non-destructive multi-element analysis of solid-state samples, which results in a significant reduction of analysis time, since no special sample treatment is needed. The possibility of application of mobile XRF systems makes this technique attractive for many purposes [5][6][7]. But in this particular case, i.e.…”
Section: Introductionmentioning
confidence: 99%